WORSHIP DISCIPLINE CHARACTER EDUCATION STRATEGY THROUGH EXTRACURRICULAR ACTIVITIES - Nurhaqim, Muhammad; Subando, Joko (Proceeding of International Conference of Islamic Education, 2023)
This study aims to determine the character education strategy for religious discipline through scout extracurricular activities at Madrasah Ibtidaiyah Negeri 3 Boyolali. The approach used in this study is a qualitative research approach and descriptive qualitative research. The reason researchers used this type of descriptive qualitative research was because they wanted to know and describe the role of scouting in relation to the discipline of worshiping students at Madrasah Ibtidaiyah Negeri 3 Boyolali. This research is aimed at describing the inculcation of discipline through scout extracurricular activities at MIN 3 Boyolali. Instilling the discipline of worship in students of MIN 3 Boyolali through observations, interviews, and documentation. Technique The validity of the data in this study was tested by triangulation. Triangulation in testing credibility is defined as checking data from various sources at various times. Thus there is triangulation of sources, triangulation of data collection techniques, and time. The results of this study indicate that the religious discipline character education strategy through extracurricular activities can be carried out in several ways including: value inculcation, exemplary, facilitation, academic and social development. While the obstacles and obstacles include: Low interest and participation, limited time and resources, challenges in integrating religious values and limited understanding and competence of mentors.